Effects of chiropractic in patients with shoulder adhesive capsulitis (frozen shoulder): review article. - Almeida, Alana Cardécia de; Basilio, Franciane Batista; Silva, Rodrigo Marcel Valentim da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: adhesive capsulitis (frozen shoulder) is a common disease that causes significant morbidity. Chiropractic care is based on technical adjustments that restore normal micro-motion to the spine, reducing neural compression cause of painful symptoms that particular dermatome. The aim of this paper is to review the scientific literature the effects of chiropractic in patients with frozen shoulder. Method: This is an integrative review article, made from primary sources. As criteria for inclusion of articles, we selected only those whose methodology was Clinical Trial Controlled Randomized, published in the period 2010 to 2016, which made reference to features and methods of the relevant chiropractic treatment of frozen shoulder, which compared a group chiropractic and another that applied conventional physiotherapy or other similar technique. Results: The search in databases totaled 18 randomized controlled trials. According to the inclusion criteria, only three articles were selected. The three studies have shown benefits of chiropractic for improvements in mobility, pain and function. Conclusion: Each article has shown benefits with the application of chiropractic techniques frozen shoulder.